2018
DOI: 10.1103/physreva.98.062301
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional measurement-device-independent quantum key distribution on two-dimensional subspaces

Abstract: Quantum key distribution (QKD) provides ultimate cryptographic security based on the laws of quantum mechanics. For point-to-point QKD protocols, the security of the generated key is compromised by detector side channel attacks. This problem can be solved with measurement device independent QKD (mdi-QKD). However, mdi-QKD has shown limited performances in terms of the secret key generation rate, due to post-selection in the Bell measurements. We show that high dimensional (Hi-D) encoding (qudits) improves the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Device‐independent (DI) protocols or measurement‐device‐independent protocols (MDI) can overcome these limitations . In this direction, two proof‐of‐concept of high‐dimensional QKD in an MDI scheme has been proposed and proved…”
Section: Quantum Communicationsmentioning
confidence: 99%
“…Device‐independent (DI) protocols or measurement‐device‐independent protocols (MDI) can overcome these limitations . In this direction, two proof‐of‐concept of high‐dimensional QKD in an MDI scheme has been proposed and proved…”
Section: Quantum Communicationsmentioning
confidence: 99%
“…According to the verification results, Alice and Bob determine what information they should keep. Due to the low generation rate of MDI protocol, high-dimensional MDI (Dellantonio et al 2018) is invented, which makes the quantum state with more information and increases the key generation rate. In fact, in quantum theory, high-dimensional quantum states can be composed of multiple two-dimensional quantum states, which is the reason why highdimensional quantum states can be converted into time-sharing two-dimensional MDI.…”
Section: And Hd-mdimentioning
confidence: 99%
“…When the error rate is high (Khan 2009;Xu et al 2020), high-dimensional quantum states can also increase the key generation rate. Hd-MDI (Dellantonio et al 2018) is also a method to deal with high loss channels.…”
Section: Channel Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also found that the efficiency of key distribution increases with qudits in an ideal situation [ 32 , 33 , 34 , 35 , 36 ]. Various high-dimensional QKD protocols have been proposed such as a generalized version of BB84, a multipartite high-dimensional QKD [ 37 ], and MDI-QKDs using high-dimensional quantum states [ 38 , 39 , 40 ]. Moreover, QKD protocols using qudits have been implemented experimentally in various quantum system, for instance, energy-time eigenstates [ 41 , 42 , 43 , 44 , 45 ] and orbital angular momentum (OAM) mode of a single photon [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%